Formononetin ameliorates polycystic ovary syndrome through suppressing NLRP3 inflammasome - Zhuo Liu; Rui-Han Wang; Ke-Hua Wang (Molecular Medicine)
Abstract Background Polycystic ovary syndrome (PCOS) is a common gynecological disease accompanied by multiple clinical features, including anovulation, hyperandrogenism, and polycystic ovarian morphology, leading to infertility. Formononetin (FMN), which is a major bioactive isoflavone compound in Astragalus membranaceus, exerts anti-inflammatory effects. However, whether FMN is effective in the treatment of PCOS remains unknown. This study aims to explore the effects and the possible mechanisms of FMN in PCOS. Methods Dehydroepiandrosterone (DHEA)-induced PCOS rats and dihydrotestosterone (DHT)-induced PCOS cell models were established. Fifty rats were randomly assigned into five groups of 10 rats each: Control, PCOS, PCOS + FMN (15 mg/kg), PCOS + FMN (30 mg/kg), and PCOS + FMN (60 mg/kg). Fasting blood glucose, insulin, luteinizing hormone, follicle-stimulating hormone, testosterone, and estradiol were detected in DHEA-induced PCOS rats. Ovarian histological changes and apoptosis were evaluated utilizing H&E and TUNEL staining. Subsequently, the effects of FMN on oxidative stress and inflammatory responses in the DHEA-induced PCOS rat model and DHT-induced PCOS cell model were explored. Besides, the function of FMN on cell viability and apoptosis in DHT-induced PCOS cell model were explored by using CCK-8 assay and flow cytometry. Protein expression was detected via western blot and immunofluorescence staining in the DHEA-induced PCOS rat model and DHT-induced PCOS cell model. Results FMN alleviated PCOS symptoms and reduced inflammation, cell apoptosis, and oxidative stress in DHEA-induced PCOS rats and DHT-induced KGN cells. Additionally, FMN suppressed NLRP3 inflammasome activation in both models. In the DHT-induced PCOS cell model, nigericin (a activator of NLRP3) reversed the functions of FMN on inflammation, apoptosis, and oxidative stress. Conclusion These findings demonstrated that FMN could alleviate PCOS by repressing inflammation, apoptosis, as well as oxidative stress in vivo and in vitro via inhibition of the NLRP3 inflammasome. Highlights 1. FMN improved PCOS symptoms. 2. FMN alleviated cell apoptosis, inflammation and oxidative stress in PCOS. 3. FMN inhibited the activation of NLRP3 inflammasome in PCOS.